Evaluation of College of Nursing Affiliates’ Knowledge about Lung Cancer and its Relationship with Smoking - almallah, nawar; Al Alwan, nada; Al Attar, wafa; Hassoun, thamera (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To evaluate knowledge towards smoking and its relationship with lung cancer among members of Baghdad Nursing College. Methodology: The study comprised 100 affiliates from the College of Nursing/ University of Baghdad that included students, teaching staff and employees. All data was collected through a structured questionnaire prepared by the National Cancer Research Center which were answered during a scientific symposium organized by the center on lung Cancer Awareness in March 2016.The data were analyzed by using the SPSS, version 22 Results: The age of the respondents ranged from (19-64 years); 76% were females and only 4% were smokers. The results showed that the mean score for the level of knowledge was 65%. The correlation coefficient between the response and the occupation was 0.03. Twenty-two percent of the participants were of average grade while 20% of the responses were of acceptable level. The calculated rates for scores good, very good and excellent responses were for 18%, 12% and 10% respectively. It was displayed that 41% expressed interest to participate in the awareness campaign under the supervision of the National Cancer Research Program; females expressed a desire for charity more than males (74%). Recommendations: To promote public awareness about the harmful effects of tobacco and the importance of preventing smoking, highlighting its relationship with lung cancer and other malignant diseases. Non Governmental organization should collaborate with the health and educational institutions to raise the level of knowledge among the Iraqi society